Breech Presentation - A scientiometric analysis of the global research output. (September 2020) - Brüggmann, Dörthe; Jaque, Jenny M.; Klingelhöfer, Doris; Groneberg, David A.; Louwen, Frank
Abstract: Objective: Although breech presentations occur in 3–5% of term deliveries, the mode of delivery still remains a topic of debate. Hence, this study aimed to analyze the worldwide research output on breech presentation. All relevant publications issued in the Web of Science from 1900 to 2014 were assessed by an objective, standardized bibliometric procedure. Study design: In this retrospective, descriptive study, we used the computerized NewQIS platform, to identify publications by a specific search term and to analyze them regarding quantitative parameters (e.g., countries of origin, journals) as well as qualitative characteristics (e.g., citation rate, country-specific H-index). In addition to geographical aspects, chronological developments and collaboration networks were investigated. In order to visualize the results, anamorphic maps were generated by the innovative "density equalizing map projections"(DEMP) technology. Results: A total of 1, 438 original articles, reviews, "Letters" and "Abstracts" on breech presentation were identified. 86% of this work was written in English. The highest number and the most cited publications came from the US and Canada as well as Western European countries. Exceptions were Israel and South Africa that appeared among the leading countries. The collaboration network included 26 countries, dominated by the US and the UK. We also present a table of the 14 most cited publications in the world. Summary: This study underlines that the mere total of only 1, 438 publications on breech do not do justice to this relevant and controversially discussed topic. The global research output was dominated by the industrialized world. Developing and emerging countries are largely excluded from research activities. To minimize this imbalance and to foster scientific collaborations, future research on this topic needs to be planned and funded according to these shortcomings.